Pragmatic or Absolute Establishment of Philosophy - Ebrahim Safabakhsh (Eidos. A Journal for Philosophy of Culture, 2023)
At the foundation of systematic thinking lie decisive assumptions that cannot be articulated and treated in a theoretical manner. Nonetheless, they are settled practically and metaphorically to orient and provoke the systematic attempts of philosophy. This field of non-theoretical assumptions is the theme of this paper. In the following, I articulate one specific metaphorical and practical answer that defies theoretical and systematic treatment. While it is among the most fundamental and fatal answers that can ever be ventured in the entire field of systematic thinking, they cannot occupy center-stage in theoretical thinking. The problematic concerns the pragmatic or absolute establishment of the edifice of philosophy. In the following, I try to portray a fundamental but irresolvable conflict in a back-and-forth movement between rival answers given to this problematic. This investigation concludes by emphasizing the irremediable failure to settle, once and for all, the conflict portrayed between the two opposed designations of philosophy in principle.